Depression among Turkish and Moroccan immigrant populations in Northwestern Europe: a systematic review of prevalence and correlates - Gabriela A. Sempértegui; Christos Baliatsas; Jeroen W. Knipscheer; Marrie H. J. Bekker (BMC Psychiatry, 2023)
Abstract Background This systematic review aimed to synthesize the prevalence and correlates of depressive disorders and symptoms of Turkish and Moroccan immigrant populations in Northwestern Europe, formulating evidence-informed recommendations for clinical practice. Methods We conducted a systematic search in PsycINFO, MEDLINE, Science Direct, Web of Knowledge, and Cochrane databases for records up to March 2021. Peer-reviewed studies on adult populations that included instruments assessing prevalence and/or correlates of depression in Turkish and Moroccan immigrant populations met inclusion criteria and were assessed in terms of methodological quality. The review followed the relevant sections of the Preferred Reporting Items for Systematic Reviews and Meta-analyses reporting (PRISMA) guideline. Results We identified 51 relevant studies of observational design. Prevalence of depression was consistently higher among people who had an immigrant background, compared to those who did not. This difference seemed to be more pronounced for Turkish immigrants (especially older adults, women, and outpatients with psychosomatic complaints). Ethnicity and ethnic discrimination were identified as salient, positive, independent correlates of depressive psychopathology. Acculturation strategy (high maintenance) was related to higher depressive psychopathology in Turkish groups, while religiousness appeared protective in Moroccan groups. Current research gaps concern psychological correlates, second- and third-generation populations, and sexual and gender minorities. Conclusion Compared to native-born populations, Turkish immigrants consistently showed the highest prevalence of depressive disorder, while Moroccan immigrants showed similar to rather moderately elevated rates. Ethnic discrimination and acculturation were more often related to depressive symptomatology than socio-demographic correlates. Ethnicity seems to be a salient, independent correlate of depression among Turkish and Moroccan immigrant populations in Northwestern Europe.